2022
DOI: 10.1021/acsami.1c23942
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Reduced Loss in High Fill Factor Inverted Perovskite Solar Cells with Methoxy-Substituted Poly(Triarylamine) as the Hole Selective Contact

Abstract: A dopant-free polymeric hole selective contact (HSC) layer is ubiquitous for stable perovskite solar cells (PSCs). However, the intrinsic nonwetting nature of the polymeric HSC impedes the uniform spreading of the perovskite precursor solution, generating a terrible buried interface. Here, we dexterously tackle this dilemma from the perspective of dispersive and polar component surface energies of the HSC layer. A novel triarylamine-based HSC material, poly­[bis­(4-phenyl)­(2,4-dimethoxyphenyl)­amine] (2MeO-PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The improved wettability implied higher surface energy for BN-6, BN-9, and BN-12 films, which benefits the formation of high-quality perovskite film. 56 Scanning electron microscopy (SEM) further probed the crystal morphology of the deposited perovskite, as shown in Figure 4c. Compared to that of PTAA, BN-3, and BN-6, the perovskite coated on the BN-9 and BN-12 films presented more sharp and larger-scale crystals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improved wettability implied higher surface energy for BN-6, BN-9, and BN-12 films, which benefits the formation of high-quality perovskite film. 56 Scanning electron microscopy (SEM) further probed the crystal morphology of the deposited perovskite, as shown in Figure 4c. Compared to that of PTAA, BN-3, and BN-6, the perovskite coated on the BN-9 and BN-12 films presented more sharp and larger-scale crystals.…”
Section: Resultsmentioning
confidence: 99%
“…The smaller contact angles suggest an increased wettability of perovskite precursor on the films of BN-6, BN-9, and BN-12 compared to that of BN-3. The improved wettability implied higher surface energy for BN-6, BN-9, and BN-12 films, which benefits the formation of high-quality perovskite film …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the methoxy substitutions were found to enhance hole-extraction capability and improve the wetting of perovskite precursor solution due to providing a hole-transfer pathway and enhancing the surface polarity, thus enabling convenient perovskite deposition and more intimate substrate−perovskite contact, leading to better performance of methoxy substituted triphenylamine-based SAMs. 30,31 Regarding the conjugated linker, we found that extension of conjugation length always resulted in improved device performance. Due to the twisted configuration of arylamine groups, especially the propeller configuration of the triphenylamine group, SAMs with short linkers have difficulty forming a dense monolayer because of strong steric hindrance, which facilitates better hole selective contact and ultimately improves the overall device parameters, especially V OC values.…”
mentioning
confidence: 88%
“…[14,15] It is, therefore, a hot topic to develop novel, low-cost, stable HTMs with equally high performance as Spiro-OMeTAD. [16][17][18][19][20][21][22][23][24][25] Macrocyclic phthalocyanines and porphyrin derivatives showed great potential as the alternative HTMs due to their high thermal/photochemical stability, easily tailored peripheral/ non-peripheral substituents, and tunable electro/photochemical properties. [26][27][28][29][30][31][32][33][34] In 2016, Yeh and co-workers demonstrated Zn II porphyrin HTM consisting of meso-5,15bis(ethynylaniline) backbones bearing bilateral butyl chains, and the resulted PSCs achieved a promising efficiency of 16.60 %, comparable to that of Spiro-OMeTAD with a PCE of 18.03 %.…”
Section: Introductionmentioning
confidence: 99%